TEATER SEBAGAI MEDIA EDUKASI DALAM MEMBENTUK KARAKTER SISWA DI SMPI AL-AZHAR 32 PADANG - Cindy Amalia Putri; Tulus Handra Kadir (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to determine the effectiveness of theatre activities as a means of fostering a spirit of mutual cooperation and collaboration among students, as well as to identify changes in the students' character in aspects of mutual cooperation and collaboration after being involved in theatre activities at SMPI Al-Azhar 32 Padang. This study employs a qualitative approach with descriptive analysis methods. The instrument used is the researcher themselves along with supporting tools such as writing materials and a camera. Data collection techniques include literature study, observation, interviews, and documentation. The steps used to analyze the data are data collection, data reduction, presentation of data, and drawing conclusions. The research findings indicate that Theatre as an Educational Medium in Shaping Student Character at SMPI Al-Azhar 32 Padang involved three activities: the Musical Drama Closing Performance of P5, the performance titled "Together We Are Strong!", and the Rainbow Musical Drama performance at the school garden. The closing performance of P5 can serve as an effective platform for fostering a spirit of mutual cooperation and teamwork among students. Through the preparation and execution of the performance, students learn to work together, support one another, and appreciate diverse opinions to achieve common goals. The theatre "Our Voice, Our Future" illustrates that the election of the student council president is not just about selecting a leader, but also about learning cooperation, responsibility, and democracy. All characters play an active role in creating a collaborative and participatory atmosphere. The play "Rainbow in the School Garden" is a performance for the opening of the class meeting with a free theme, during which a cleanliness competition between classes is taking place. One of the main strengths of this theatre is the use of cheerful and spirited songs. Songs such as "One Team, One Goal", "Hands Together", and "Rainbow in Our Garden" not only uplift the mood but also convey a moral message about the values of responsibility, courage, and honesty.